From digital traces to public vaccination behaviors: leveraging large language models for big data classification - Oh, Yoo Jung; Rasul, Muhammad Ehab; McKinley, Emily; Calabrese, Christopher (Frontiers in Artificial Intelligence, 2025)
IntroductionThe current study leverages large language models (LLMs) to capture health behaviors expressed in social media posts, focusing on COVID-19 vaccine-related content from 2020 to 2021.MethodsTo examine the capabilities of prompt engineering and fine-tuning approaches with LLMs, this study examines the performance of three state-of-the-art LLMs: GPT-4o, GPT-4o-mini, and GPT-4o-mini with fine-tuning, focusing on their ability to classify individuals’ vaccination behavior, intention to vaccinate, and information sharing. We then cross-validate these classifications with nationwide vaccination statistics to assess alignment with observed trends.ResultsGPT-4o-mini with fine-tuning outperformed both GPT-4o and the standard GPT-4o-mini in terms of accuracy, precision, recall, and F1 score. Using GPT-4o-mini with fine-tuning for classification, about 9.84% of the posts (N = 36,912) included personal behavior related to getting the COVID-19 vaccine while a majority of posts (71.45%; N = 267,930) included information sharing about the virus. Lastly, we found a strong correlation (r = 0.76, p < 0.01) between vaccination behaviors expressed on social media and the actual vaccine uptake over time.DiscussionThis study suggests that LLMs can serve as powerful tools for estimating real-world behaviors. Methodological and practical implications of utilizing LLMs in human behavior research are further discussed.